LEARNERS' PERCEPTION ON INDONESIAN MORPHOLOGY-SYNTACTIC INTERFERENCE DONE BY ENGLISH LECTURERS-A CASE STUDY IN HIGHER EDUCATION - Nurhayati, Dwi Astuti Wahyu; Djatmika, .; Santosa, Riyadi; Wiratno, Tri (PEOPLE: International Journal of Social Sciences, 2017)
This paper investigated English language learning teaching learners’ perception on Indonesian Morphology-Syntactic Interference done by English lecturers. The study was done through a survey to 249 ELLT learners towards 10 English lecturers State Islamic Institute and PGRI Teacher Training College of Tulungagung, East Java,Indonesia. Quantitative results showed that the way English lecturers delivered the materials was influenced by the Indonesian structure. Focusing on Indonesian structure may be true to make it easier for the learners to understand the materials, but it is not the only case in colleges where many English lecturers intend to mix Indonesian and English structures, grammatical translation method to enable the students to understand the learning material. The findings revealed that the respondents believed English lecturers tended to use their way of communication in the perspective of learning strategy. This suggests that English lecturers should do Self Professional Development.